The sensitive left and the impervious right: Multilevel models and the politics of inequality, ideology, and legitimacy in Europe - Christopher J. Anderson; Matthew M. Singer (Luxembourg Income Study (LIS), 2008)
While comparative politics has been dominated by macro-approaches, relatively little comparative scholarship has focused on understanding the behavior of individuals. However, recent years have seen increased attention to integrating what we know about individual citizens with what we know about macro-level contexts that vary across countries. This research examines how people's interpretations, opinions, and actions are shaped by and embedded in variable contextual parameters (structural, institutional, cultural). This article discusses the growing literature on the nexus of macro-level context and individual behavior and the potential for integrating existing knowledge, as well as some of the challenges inherent in multilevel analyses. It also provides a novel substantive application. Using surveys conducted in 2002-03 in 20 European democracies, we examine the effect of income inequality on people's attitudes about the functioning of the political system and trust in public institutions. We find that citizens in countries with higher levels of income inequality express more negative attitudes toward public institutions. Moreover, we show that the negative effect of inequality on attitudes toward the political system is particularly powerful among individuals on the political left. In contrast, inequality's negative effect on people's faith in the system is muted among those on the right.
Keywords: 330